2015
DOI: 10.17559/tv-20140128231244
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study on the use of fractal analysis for evaluating the surface quality generated by waterjet

Abstract: Original scientific paper The paper presents the fractal analysis application for a simple evaluation of the quality of waterjet treated surfaces, especially after abrasive waterjet cutting. This analysis will enable the elimination of subjective assessments of treated surfaces. This will ensure a clear estimate of the quality of the surface and the ability to objectively compare the quality of the cutting edge obtained by using different cutting parameters. Keywords: fractals analysis; fractal dimension; surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…1b), causes increase cutting efficiency. As a result, it becomes possible to almost any material cutting with low roughness of cutting surface [13,16,20]. The most commonly used pressure in the system, called AWJ, ranges from 400 to 600 MPa and common abrasive is garnet [2,11].…”
Section: Introductionmentioning
confidence: 99%
“…1b), causes increase cutting efficiency. As a result, it becomes possible to almost any material cutting with low roughness of cutting surface [13,16,20]. The most commonly used pressure in the system, called AWJ, ranges from 400 to 600 MPa and common abrasive is garnet [2,11].…”
Section: Introductionmentioning
confidence: 99%
“…They discovered that corundum, which was approximately equal to garnet, increased cutting speed at 20%. Garnet has a comparatively low wear of focusing tubes when utilized [90]. A survey reported that 90% of users employ garnet as an abrasive type during AWJM applications [4].…”
Section: Abrasive Systemmentioning
confidence: 99%
“…Where, D is fractal dimension, C is constant value. The fractal dimension can be calculated from the equation [11]:…”
Section: Laser Speckle Techniquementioning
confidence: 99%